Bilateral laryngeal paralysis following a ventral slot surgery in a dog. Issue 2 (16th June 2020) - Rodriguez, Alfonso; Beltran, Elsa; Sanchis‐Mora, Sandra; Palacios, Carolina
Abstract : An English springer spaniel developed laryngeal paralysis immediately after a ventral slot decompression surgery to treat an intervertebral disc extrusion that was causing a C1–T2 myelopathy with cervical hyperaesthesia. Postsurgical stabilisation in the intensive care unit is described. This included mechanical ventilation, tracheostomy tube placement and care, and laryngeal tie‐back surgery aftercare. Common complications after ventral slot decompression include pain, severe haemorrhage and deterioration in the neurological status. Laryngeal paralysis has not yet been reported in dogs after a ventral slot.